Coffee Improvement by Wet Fermentation Using Lactobacillus plantarum: Sensory Studies, Proximate Analysis, Antioxidants, and Chemical Compounds - Latief, Madyawati; Maharani, Rizky; Tarigan, Indra Lasmana; Sutrisno, Sutrisno (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2023)
Fermentation has been developed to produce a distinctive taste in food, one of which is coffee. Fermentation affects the quality and taste of coffee in coffee beans. This study conducted coffee fermentation using Lactobacillus plantarum bacteria, isolates of Lactic Acid Bacteria. The research method begins with the preparation of Lactobacillus plantarum inoculants which will be used for coffee fermentation, fermentation, total phenol and flavonoid content, caffeine content, chlorogenic acid content, compound analysis, antioxidants, and proximate analysis. Total phenol and flavonoid, caffeine, chlorogenic acid, and antioxidant using the UV-VIS Spectrophotometer instrument. In addition, compound analysis is carried out using GC-MS. This study showed that the bacterium Lactobacillus plantarum would hydrolyze sucrose into simpler sugars with the enzyme invertase and produce organic acids through glycolysis. Liberica coffee fermented using Lactobacillus plantarum bacteria contains phenol compounds, flavonoids, antioxidants, and compound compounds higher than Original Liberica coffee. Meanwhile, the caffeine and chlorogenic acid of Liberica coffee fermented using Lactobacillus plantarum bacteria are lower than Original Liberica coffee. Overall, the chemical compounds of Liberica coffee that have been fermented using Lactobacillus plantarum bacteria are better than Original Liberica Coffee. Liberica coffee beans fermented using Lactobacillus plantarum bacteria have better physical quality and taste than Original Liberica coffee